Enhanced Degradation of Dyes present in Textile Effluent by Ultrasound Assisted Electrochemical Reactor - Asad Ali; Naeem Ejaz; Sadia Nasreen; Ali Nasir; Liaqat Ali Qureshi; Basem Mohammed Al-Sakkaf (Salehan Institute of Higher Education, 2019)
Textile industry being the backbone of any country plays a very essential part in the development of the country. The treatment of chemical dyes present in textile wastewater and its reuse for irrigational purposes has become a major concern for the researchers. The present study emphasis on proper degradation of commonly used reactive blue (RB) 19 dye present in textile effluents using ultrasound assisted electrochemical reactor technique and presenting the analysis of microparticles present in dyes and its quantitative composition before and after treatment by means of scanning electron microscopy (SEM) images at high magnification. The investigation was carried out using various parameters such as Concentration, pH and reaction rate. The testing setup also includes UV absorbance spectrophotometer, ultrasonic bath, DC power supply, weighing balance, suction apparatus, and thermometer. Our studies show that the Optimum dye degradation (i.e. 82.3 %) was achieved at time 120 minutes with pH of 3.22 for 50 ppm of solution and the maximum degradation (i.e. 85%) was achieved at 40 0C using acid (HCl) and Base (NaOH) in equal amounts after 120 minutes for solution of 30ppm. The work efficiency includes saving time, money and degrading the dyes from wastewater before toxic sludge formation.